Rectal Cancer Incidence is Low Following Rectal Diversion or Subtotal Colectomy for IBD: Results of a Population-based Study. (17th May 2021) - Brar, Mantaj S; de Buck van Overstraeten, Anthony; Baxter, Nancy N
Abstract: Background and Aims: Following subtotal colectomy or diversion for medically refractory inflammatory bowel disease [IBD], completion proctectomy has been recommended to reduce the risk of rectal cancer. However, this recommendation is based on low-quality evidence. Our objectives were to estimate the cumulative incidence of rectal cancer and evaluate if surveillance endoscopy reduces the risk of rectal cancer. Methods: We performed a population-based retrospective cohort study in Ontario, Canada, of all patients undergoing either subtotal colectomy or diversion for medically refractory IBD over 1991–2015. We excluded patients with a previous history of colorectal cancer or previous rectal resection, and those with <1 year of observation. We calculated the rate of incident rectal cancer using a competing risks model, and evaluated the effect of surveillance endoscopy on the rate of rectal cancer. Results: In all, 3700 patients were included with a median follow-up of 4.3 years. Of this cohort, 47% underwent rectal resection or restoration of gastrointestinal [GI] continuity during the observation period; 40 patients were diagnosed with rectal cancer, with a cumulative incidence of rectal cancer of 0.81% (95% confidence interval [CI] 0.53%, 1.20%) and 1.86% [95% CI 1.29%, 2.61%] at 10 and 20 years, respectively. Surveillance endoscopy was associated with a lower rate of rectal cancer (subhazard ratio [sHR] 0.37, 95% CI 0.16, 0.82, p = 0.014]. Conclusions: Among patients with a retained rectum following surgery for IBD, the risk of rectal cancer is low and appears to be lower when surveillance endoscopy is performed. Expectant management with surveillance endoscopy may be a reasonable alternative to completion proctectomy in selected patients.